Pension Funds for Housing Development in Indonesia: Challenges and Strategies - Soseco, Thomas; Kresnowati, Anggari Marya; Rini, Ayu Dwidyah (Economics and Finance in Indonesia, 2025)
Housing infrastructure is necessary to improve the quality of life of the community, yet a recent assessment of housing infrastructure development in Indonesia highlights a low level of performance. Therefore, actions are needed to stimulate it through pension funds, which remain minimally utilized for direct investment in the housing sector. This research investigates the potential and challenges of using pension funds for housing investment in Indonesia, employing Input Output (IO) Analysis with data from Statistics Indonesia (BPS). The findings reveal a significant gap between the potential and realized pension fund investments, indicating the substantial capacity of pension funds to be directed towards investment in the housing sector. Two strategies are recommended to address this. First, maximizing pension fund revenue, mainly among population groups underserved by pension funds, such as micro, small, and medium business owners and informal workers. Second, reorienting policies to enhance investment opportunities in the housing sector while overcoming future challenges.